Vertical profile measurements of lower troposphere ionisation - Harrison, R; Nicoll, K; Aplin, K (Elsevier, 2014)
Vertical soundings of the atmospheric ion production rate have been obtained from Geiger counters integrated with conventional meteorological radiosondes. In launches made from Reading (UK) during 2013-2014, the Regener-Pfotzer ionisation maximum was at an altitude equivalent to a pressure of (63.1±2.4)hPa, or, expressed in terms of the local air density, (0.101±0.005)kgm-3. The measured ionisation profiles have been evaluated against the Usoskin-Kovaltsov model and, separately, surface neutron monitor data from Oulu. Model ionisation rates agree well with the observed cosmic ray ionisation below 20km altitude. Above 10km, the measured ionisation rates also correlate well with simultaneous neutron monitor data, although, consistently with previous work, measured variability at the ionisation maximum is greater than that found by the neutron monitor. However, in the lower atmosphere (below 5km altitude), agreement between the measurements and simultaneous neutron monitor data is poor. For studies of transient lower atmosphere phenomena associated with cosmic ray ionisation, this indicates the need for in situ ionisation measurements and improved lower atmosphere parameterisations.